Age, growth, and maturity of the Indian flathead Platycephalus indicus in the waters around Okinawa-jima Island, Japan - Akita, Yuichi; Tachihara, Katsunori (Ichthyological research, 2019)
Indian flathead Platycephalus indicus (Platycephalidae) is an important fishery resource in tropical and subtropical waters. However, there have been few studies of its life history which is important for resource management because of taxonomic confusion. Here, we determine the age, growth, maturity, and spawning season of P. indicus from 351 specimens [21.7–76.9 cm total length (TL) for females; 19.6–61.9 cm TL for males] collected between August 2006 and August 2009 around Okinawa-jima Island, in southern Japan. Almost all specimens were caught by artisanal fishery. Age was determined by sectioning otoliths: the oldest specimens were seven years in both sexes. Parameters for von Bertalanffy growth functions were L ∞ = 72.6, k = 0.48 and t 0 = -0.36 for females, and L ∞ = 53.6, k = 0.68 and t 0 = -0.38 for males. Mean body size of females was larger than males at a given age, indicating females grow larger than males. The spawning season was estimated to be between January and October. The smallest and youngest mature female was 36.1 cm TL and 1.0 year old, while the smallest and youngest male was 22.9 cm TL and 0.4 years old. Moreover, the smallest mature male individual was smaller than the smallest female. Furthermore, we did not observe hermaphroditic gonads. Therefore, we consider that discrepancy in body size between sexes results from the difference in growth rate rather than sex change.